IMPLEMENTING RISK MANAGEMENT IN EDUCATIONAL INSTITUTIONS: APPROACHES AND BEST PRACTICES - Jemmy Jemmy; Selamet Riyadi (International Journal of Teaching and Learning, 2025)
This study examines the implementation of risk management in educational institutions, focusing on approaches and best practices to enhance risk preparedness and response. Risk management in education involves systematically identifying, assessing, and addressing potential threats that could disrupt institutional operations. Through an extensive literature review, this research highlights key strategies, such as regular risk assessments, staff training, technological integration, stakeholder involvement, and comprehensive policy development. These approaches have proven effective in strengthening institutional resilience, improving operational efficiency, and enhancing disaster preparedness. The findings indicate that adopting robust risk management frameworks significantly enhances safety, operational continuity, and disaster readiness in educational institutions. Additionally, the study underscores the importance of stakeholder participation and the development of clear, comprehensive policies. The practical implications include improving safety and operational performance, while the theoretical contributions advance cohesive and adaptive risk management frameworks. Future research could focus on longitudinal studies to evaluate the long-term impact of these strategies, comparative analyses across different types of institutions, and further exploration of technology’s role in risk management. By recognizing the importance of risk management and adopting best practices, educational institutions can better prepare for future challenges, providing a safer and more effective learning environment for all stakeholders.